2016
DOI: 10.3390/v8110319
|View full text |Cite
|
Sign up to set email alerts
|

Pathogens Inactivated by Low-Energy-Electron Irradiation Maintain Antigenic Properties and Induce Protective Immune Responses

Abstract: Inactivated vaccines are commonly produced by incubating pathogens with chemicals such as formaldehyde or β-propiolactone. This is a time-consuming process, the inactivation efficiency displays high variability and extensive downstream procedures are often required. Moreover, application of chemicals alters the antigenic components of the viruses or bacteria, resulting in reduced antibody specificity and therefore stimulation of a less effective immune response. An alternative method for inactivation of pathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(74 citation statements)
references
References 30 publications
2
68
1
1
Order By: Relevance
“…Calibration was carried out in a petri dish system using a foil of oriented polypropylene (OPP) to generate a thin liquid layer (approx. 85 μm) of TTC irradiated with a very low dose gradient of 13% 23 . For the irradiation with the slit diaphragm, a dose reduction of 99% was measured.…”
Section: Measurement Of Liquid Heightmentioning
confidence: 99%
“…Calibration was carried out in a petri dish system using a foil of oriented polypropylene (OPP) to generate a thin liquid layer (approx. 85 μm) of TTC irradiated with a very low dose gradient of 13% 23 . For the irradiation with the slit diaphragm, a dose reduction of 99% was measured.…”
Section: Measurement Of Liquid Heightmentioning
confidence: 99%
“…We have previously shown that LEEI can successfully be used to inactivate a number of pathogens, such as influenza (H3N8), Equid herpesvirus 1, porcine reproductive and respiratory syndrome virus (PRRSV) or respiratory syncytial virus (RSV) [13,17]. Here we report that a bacterin including the LEEI-inactivated Gram-negative pathogen R. pneumotropicus elicited a prominent humoral immune response and protection against infection of the lower respiratory tract in mice, the natural host.…”
Section: Discussionmentioning
confidence: 92%
“…This makes LEEI applicable in normal laboratory settings. We have shown previously that LEEI can be used to generate efficient vaccines against viruses and parasites [13,17,18]. To evaluate the potential of LEEI for the development of bacterins with increased protective efficacy, we chose a challenge experiment with R. pneumotropicus in its natural host, the mouse.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the effect on the proteins can be reduced with the use of electron, but electron irradiation is less penetrating than gamma rays [15]. In contrast to high energy electron (>1 MeV), the low energy electron irradiation (LEEI, <500 keV), does not generate x ray radiation and thus, does not require complex shielding [18]. LEEI works efficiently in inactivation of different viruses such as (influenza A (H3N8) and porcine reproductive and respiratory syndrome virus (PRRSV) [18].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to high energy electron (>1 MeV), the low energy electron irradiation (LEEI, <500 keV), does not generate x ray radiation and thus, does not require complex shielding [18]. LEEI works efficiently in inactivation of different viruses such as (influenza A (H3N8) and porcine reproductive and respiratory syndrome virus (PRRSV) [18]. On the other hand, ultraviolet radiation demonstrated an efficient role in inactivation of the enveloped MHV coronavirus [19], the enteric human adenovirus (HAdV) reported to be the most UVresistant virus [20].…”
Section: Introductionmentioning
confidence: 99%